The effect of compound training according to the electrical activity in the motor ability of the muscles of the legs of runners 200m running event for youth (Journal of the College of Basic Education, 2023)
Introduction and the importance of the research - the researcher chose one of the most training methods that help in developing the systolic efficiency of the working muscles, which is compound training, which has proven wide successes for most trainers and researchers who used it in developing muscular capacity. Working through electrical activity (EMG device) for the motor performance of the two phases of starting from sitting and the phase of gradient with speed for the 200-meter run event, which is the most critical phase in achieving winning the speed races.